2009
DOI: 10.6028/nist.ir.7656
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of refrigeration systems used for vaccine storage

Abstract: Each year, billions of dollars of vaccines are stored in refrigerators at the facilities of a variety of medical providers. Many vaccines must be maintained in the range 2 °C to 8 °C to retain product potency. We have tested the performance of two types of refrigerators to determine if these refrigerators are suitable to this task, and to identify proper storage and temperature monitoring methods. Nineteen calibrated Type T thermocouples, distributed through the refrigerator interior, served as reference therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This information is reported in table 4 below. These results are similar to those obtained in power outage trials of the large pharmaceutical refrigerator unit [2]. During a power outage event, both the small and large pharmaceutical grade refrigerators warmed up to temperatures above 8 °C much more quickly than the household grade units that were tested.…”
Section: Effect Of a Power Outagesupporting
confidence: 78%
See 1 more Smart Citation
“…This information is reported in table 4 below. These results are similar to those obtained in power outage trials of the large pharmaceutical refrigerator unit [2]. During a power outage event, both the small and large pharmaceutical grade refrigerators warmed up to temperatures above 8 °C much more quickly than the household grade units that were tested.…”
Section: Effect Of a Power Outagesupporting
confidence: 78%
“…This study supplements our previous refrigerator studies of dormitory-style, freezer-less, dual-zone and large pharmaceutical grade refrigerator units [1,2]. We have followed the same approach as in our preceding studies, installing 19 NIST-calibrated, Teflon-insulated, Type T thermocouples in various locations inside the refrigerator to determine the spatial temperature distribution throughout the unit's interior.…”
Section: Experimental Methodsmentioning
confidence: 86%
“…The most sensitive vaccines are hepatitis B vaccines with a freezing threshold of -0.5 °C [ 2 ]. A thermal analysis of frequently used types of refrigerators by the US Department of Commerce [ 22 , 23 ] showed that vaccine vial temperatures vary depending on the refrigerator type, loading density and location of vaccines inside the refrigerator. Typical refrigerators used in German primary care are the types “freezerless” (single refrigerator compartment without a freezer) and “dual zone” (separate compartments for refrigerator and freezer, both with individual doors), both so-called domestic refrigerators.…”
Section: Methodsmentioning
confidence: 99%
“…Typical refrigerators used in German primary care are the types “freezerless” (single refrigerator compartment without a freezer) and “dual zone” (separate compartments for refrigerator and freezer, both with individual doors), both so-called domestic refrigerators. Based on different scenarios, that is, door openings and loading density, temperatures can vary by +/-2.3 °C in the type “freezerless” and by +/-4.5 °C in the type “dual zone” [ 22 , 23 ]. The maintenance of the temperature range of +2 to +8 °C, as recommended by vaccine manufacturers and public health authorities worldwide, is hence justified and therefore serves as a primary outcome measure.…”
Section: Methodsmentioning
confidence: 99%
“…1 To ensure that vaccines are not damaged or compromised the Centers for Disease Control and Prevention (CDC) have issued protocols to ensure proper handling, which specifies that the temperature of stored inventories must be regularly and accurately monitored to ensure that the vaccine temperature remains within specified limits. 2,3 Temperature monitoring is complicated by the fact that the raw data received by the thermistor in the refrigerator can be misleading. An unweighted temperature probe e.g.…”
Section: Introductionmentioning
confidence: 99%